Endogenous Fluorescence Tagging by CRISPR. Issue 11 (November 2019) - Bukhari, Hassan; Müller, Thorsten
Abstract : Fluorescent proteins have revolutionized biomedical research as they are easy to use for protein tagging, cope without fixation or permeabilization, and thus, enable live cell imaging in various models. Current methods allow easy and quick integration of fluorescent markers to endogenous genes of interest. In this review, we introduce the three central methods, zinc finger nucleases (ZFNs), transcription activator-like effectors (TALENs), and CRISPR, that have been widely used to manipulate cells or organisms. Focusing on CRISPR technology, we give an overview on homology-directed repair (HDR)-, microhomology-mediated end joining (MMEJ)-, and nonhomologous end joining (NHEJ)-based strategies for the knock-in of markers, figure out recent developments of the technique for highly efficient knock-in, and demonstrate pros and cons. We highlight the unique aspects of fluorescent protein knock-ins and pinpoint specific improvements and perspectives, like the combination of editing with stem cell derived organoid development. Highlights: Endogenous protein tagging allows low artificial analysis of gene expression, protein function, protein–protein interaction, cleavage, and degradation. Gene editing is used to knock-in fluorescent proteins for live imaging. GFP knock-in offers uniqueness as compared to generic editing. Organoids from edited iPS cells enable spatiotemporal monitoring of specific proteins in human brain-like tissue.